Peran “E-PPT PAJAKKU” Dalam Penghitungan Pajak JHT Serta Prosedur Percetakan Voucher Klaim Jaminan Melalui Website “SMILE” Pada BPJS Ketenagakerjaan Kantor Cabang Mojokerto - Khoirun Nisak Shabira; Nurul Azizah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This research aims to find out the procedure for calculating JHT tax and printing guarantee claim vouchers. The research method used in this journal uses data collection techniques in the form of observation, interviews and documentation. The results of this research show that the role of E-PPT My Tax in calculating JHT tax and the procedure for printing guarantee claim vouchers can make it easier for a company to record financial reports sequentially and in detail. Having procedures makes it easier to carry out an activity accurately, consistently and relevantly. The conclusion of this research is that the role of E-PPT My Tax in calculating JHT tax and the procedure for printing guarantee claim vouchers is very important because you can know how to calculate tax in detail and by printing guarantee vouchers, a company's financial reports can be directed and clear, and later An archive will also be created if the file is used at any time.